A criação do instituto federal de educação, ciência e tecnologia da Paraíba e a avaliação das repercussões na gestão de sua administração central - Correia, Vilanni Cavalcanti Dias (2017)
The Federal Network of Vocational, Scientific and Technological Education has its origin in the beginning of century XX, when in 1909 the Schools of Apprentice Craftsmen are created. In the course of their trajectory, these schools receive numerous nomenclatures, while changing to meet the complex demands of society. Recently, we have had a significant change, which has had repercussions not only on the educational dynamics of the Professional, Scientific and Technological Education (EPCT) institutions but also on their management. Thus, the present study aimed to analyze the repercussions of the public policy of transformation of the Federal Center for Technological Education of Paraíba (Cefet-PB) into the Federal Institute of Education, Science and Technology of Paraíba (IFPB) in the scope of the Central Administration of this institution in order to contribute to the evaluation of this policy. By the way, this study used documentary research, represented by laws, ordinances and data extracted from government systems and management reports from the period of 2006 to 2015. Semi-structured interviews were also conducted with the purpose of analyzing the perception of Managers in this transition process. This research emphasized the historical process of building the Federal Network of Vocational, Scientific and Technological Education, taking into account the social, economic and political context in which it occurred. Considering that the repercussions of the creation policy of the IFPB had unfolded in the most diverse segments of the institution, it was decided to deepen in the evaluation of the repercussions occurred within the administration of the IFPB. In order to do so, the following dimensions or structuring axes were considered: IFPB Creation Policy, Human Resources, Budget and Finance and Physical and Organizational Infrastructure. From the documentary analysis and the perspective of the interviewees, it was noticed that the new institutional structure of the IFPB had an impact on its management. It was found that there was not a wide participation of the community in the idealization of the policy and that its implementers did not participate, in the majority, in programs of previous qualification. However, it was considered that the results achieved were eminently positive, but inconsistencies were also found in the conduct of the policy in focus. Following the creation of the IFPB, a series of changes were observed, among which we can highlight: the restructuring of the organizational infrastructure, which favored its decentralization; the expansion of the physical structure to meet the expansion process and to adapt to the new organizational arrangement; The increase of human resources and the establishment of training policies; and the increase of administrative and budgetary autonomy and the growth of the budget to meet the new demands.